Epidemiology, outcomes and predictors of mortality in patients transported by ambulance for dyspnoea: A population‐based cohort study. (2nd August 2022) - Zhou, Jennifer; Nehme, Emily; Dawson, Luke; Bloom, Jason; Nehme, Ziad; Okyere, Daniel; Cox, Shelley; Anderson, David; Stephenson, Michael; Smith, Karen; Kaye, David M; Stub, Dion
Abstract: Objectives: There are currently limited data to inform the management of patients transported by emergency medical services (EMS) with dyspnoea. We aimed to describe the incidence, aetiology and outcomes of patients transported by EMS for dyspnoea using a large population‐based sample and to identify factors associated with 30‐day mortality. Methods: Consecutive EMS attendances for dyspnoea in Victoria, Australia from January 2015 to June 2019 were included. Data were individually linked to hospital and mortality records to determine incidence, diagnoses, and outcomes. Factors associated with 30‐day mortality were assessed using multivariable logistic regression. Results: During the study period, there were 2 505 324 cases attended by EMS, of whom 346 228 (14%) met inclusion criteria for dyspnoea. The incidence of EMS attendances for dyspnoea was 1566 per 100 000 person‐years, and was higher in females, older patients and socially disadvantaged areas. Of the 271 204 successfully linked cases (median age 76 years; 51% women), 79% required hospital admission with a 30‐day mortality of 9%. The most common final diagnoses (and 30‐day mortality rates) were lower respiratory tract infection (13%, mortality 11%), chronic obstructive pulmonary disease (13%, mortality 6.4%), heart failure (9.1%, mortality 9.8%), arrhythmias (3.9%, mortality 4.4%), acute coronary syndromes (3.9%, mortality 9.5%) and asthma (3.2%, mortality 0.5%). Predictors of mortality included older age, male sex, pre‐existing chronic kidney disease, heart failure or cancer, abnormal respiratory status or vital signs and pre‐hospital intubation. Conclusion: Dyspnoea is a common presentation with a broad range of causes and is associated with high rates of hospitalisation and death. Abstract : We performed a large retrospective population‐based cohort study of all emergency medical services (EMS) attendances for dyspnoea in Victoria, Australia over a 4.5‐year period. We found that dyspnoea is a common symptom accounting for one in seven EMS attendances, and more commonly affects females, the elderly and areas of socioeconomic disadvantage. Patients transported by EMS with dyspnoea have a high morbidity and mortality, with over three quarters admitted to hospital and a 9% mortality rate at 30 days.